Last Word on Viewpoint: Rejuvenation of the term sarcopenia - Bülow, J; Ulijaszek, S; Holm, L (American Physiological Society, 2019)
We thank all the commentators for their very valued observations. One of the main purposes of our 49 Viewpoint is to initiate debate concerning the phenomenon of Sarcopenia. About half of the commentators 50 agree with our suggestion on returning to the original definition, but emphasizing the importance of 51 acknowledging other important factors which contribute to impairment of muscle strength and function, and 52 subsequently to impaired physical capabilities. In general, these commentators suggest that these factors be 53 named and considered separately to loss of muscle mass. Conversely, the other half of commentators favor 54 the clinical usefulness of the present definition of Sarcopenia and are comfortable with the multivalent nature 55 of this definition.